Fatty Acid and Related Potassium Kv2 Channel Blockers: Toxicity and Physiological Actions on Mosquitoes - Fabien Démares; Quentin Coquerel; Gary Richoux; Kenneth Linthicum; Jeffrey Bloomquist (Insects, 2018)
Potassium channels constitute a very diverse group involved in neural signaling, neuronal activity, membrane potential maintenance, and action potential generation. Here, we tested the mammalian potassium channel blockers TRAM-34 and 5-hydroxydecanoate (5-HDC), as well as certain fatty acids (FA) that might fit in the lumen of the pore and block channel activity by obstructing K+ ion passage. Kv channel blockers could be leads for a novel pesticide type. Insecticidal activity was assessed by topical application to Anopheles gambiae adult mosquitoes, paralysis in a headless larval assay, at the cellular level with patch-clamp recordings of engineered HEK cells expressing AgKv2.1 channels, as well as central nervous system recordings from larval Drosophila melanogaster. With only one hydroxyl group difference, decanoic acid had a consistently greater effect than 5-HDC in blocking Kv channels, paralyzing larvae, and killing mosquitoes. The 11-dansylamino undecanoic acid (DAUDA) blockage of eukaryotic Kv channels is demonstrated for the first time, but it failed to kill adult mosquitoes. We synthesized alkyl esters from DAUDA and decanoic acid in an effort to improve cuticular penetration, but it had little impact upon adult toxicity. TRAM-34 and rolipram did not show activity on Kv channels nor potent insecticidal effect on adult mosquitoes. Furthermore, co-application of test compounds with permethrin did not increase mortality in adults. In conclusion, the compounds tested had modest insecticidal and synergistic activity.